Analisis Terjadinya Luka Diabetik Pada Penderita Diabetes Melitus - M. Khalid Fredy Saputra; Masdarwati Masdarwati; Nursyamsi Norma Lala; Santalia Banne Tondok; Rahmat Pannyiwi (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Diabetes Mellitus is a metabolic disorder caused by various causes and characteristics of chronic hyperglycemia accompanied by impaired carbohydrate, fat and protein metabolism resulting from impaired insulin secretion or insulin action. Purpose: Knowing the influence of diabetic wounds on people with Diabetes Mellitus. Method: Quantitative research with analytical survey design with a cross-sectional study approach. Results: Shows the results of the obesity statistical test p-value: 0.001, diet p-value: 0.000, age p-value: 0.000, physical activity p-value: 0.000. Conclusion: Obesity, diet, age and activity affect the occurrence of diabetic wounds in people with Diabetes Mellitus. Increase public knowledge about diabetes mellitus by providing counselling so the community can avoid the disease.